The Age of calamity : AD 1300-1400 - Time-Life Books (Amsterdam : Time-Life Books, 1989)
1. World history--AD1300-1400
Includes bibliographical references.
Bibliography: p. 168-169.
Basic Ed. Students
Keywords: Fourteenth century; Disasters -- History